Production of Exopolysaccharide from Lactobacillus plantarum B2 in Mulberry Based Probiotic Product - Zubaidah, Elok; Liasari, Yusnita; Saparianti, Ella (Jurnal Teknologi Pertanian, 2008)
Some microbe, including of lactic acid bacteria probiotic, has ability to produce exopolysaccharides (EPS).  Recently, researches on the ability of lactic acid bacteria that produces exopolysaccharides have still been focused only on milk, and haven’t been known how much EPS  produced by lactic acid bacteria in fruit and vegetable. Fermentation in mulberry extract is diversification of such fruit. By adding Lactobacillus plantarum B2 as EPS producer in mulberry extract, expectedly it could be fermented drink that gives multifunctional healthly effect, probiotic, exopolysaccharide, and anthocyanin. The aims of this research were to determine the effect of kinds of sugar and (NH4)2HPO4 (diamonium hidrogen phospat) concentration to EPS production of L. plantarum B2 when grown in mulberry extract. This research was conducted in randomized block design with two factors. First factor was kind of sugar that consist of glucose, sucrose, and lactose. The second factor was (NH4)2HPO4 (diamonium hidrogen phospat) concentration (0,10%; 0,20%; and 0,30%). Each treatment was done in three replications. The result was analyzed using analysis of variance (ANOVA) within 1% and 5% interval of confidence, and then continued by BNT or DMRT test. The best treatment searched by Multiple Attribute method. The result showed significant difference of kind sugar treatment on total sugar, total EPS, total acid, pH, and total LAB. Diamonium hidrogen phospat concentration treatment showed significant difference on total LAB, total N, total EPS, pH, total acid, total anthocyanin, and color intensity (L*, a*, b*). Interaction of both treatments gave no significant difference on all parameters. The best treatment resulted from the combination of 0,20% (NH4)2HPO4 concentration and lactose treatment with characteristics viability of L. plantarum B2 of 7,28 x 108 CFU/ ml, total EPS of 2105 mg/L, total acid of 0,54 %, total sugar of 6,61%, pH of 4,33, total N of 0,0209%, total anthosyanin of 190,73 mg/L, brightness level (L*) of 23,73, redness level (a*) of 8,40, dan yellowish level (b*) of 8,90.Keywords: exopolysaccharides, probiotic product, mulberry